The southwesternmost record of late Silurian (Pridolian) early land plants of Gondwana - Drovandi, Juan Martín (2024)
The Silurian–Devonian transition played a crucial role in the development of early terrestrialecosystems due to the rapid diversification of early vascular plants. However, records of Pridolianplants in western Gondwana are scarce, limited to outcrops located in southern Bolivia. In thiscontribution, an association of fossil plants housed in the Rinconada Formation is presented. Thisassociation corresponds to primitive fossil flora with reproductive structures and sterile axes linkedto basal tracheophytes. The fossil assemblage is composed of Aberlemnia caledonica, Caia langiiCooksonia cf. cambrensis, C. paranensis, C. cf. pertoni, Hostinella sp, Cf. Isidrophyton sp, Salopellamarcensis, Steganoteca striata, two morphotypes of doubtful taxonomy, and graptolites colonies. Theassociation between flora remains and graptolites, represents a parautochthonous assemblage in aninner marine platform, dominated by gravity flows. This record has paleophytogeographic importanceindicating the extension of the northwest Gondwana-southern Laurusia unit to more southern areasof Gondwana. This expansion would have been favored by the post-glacial climatic improvement ofthe Late Silurian, together with a great radiation capacity and environmental flexibility of the flora.Furthermore, the biochron is extended of three taxa (A. caledonica, C. paranensis and Cf. Isidrophytonsp) first known from the Lochkovian, to the Pridoli.